PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI PRODUKSI GULA MERAH DI DESA HUTATINGGI, KECAMATAN PUNCAK SORIK MERAPI, MANDAILING NATAL - Rizky Auliya Nasution; Kholidah Nur; Lubis, M. Raihan; Asrofi Asrofi; Andrian Matondang; Yusni Zakiah; Riski Rahmadani; Inkrid Alia; Ananda Aulia; Dina Dwi; Alvini Riska (CV. Denasya Smart Publisher, 2025)
This study aims to analyze the role of the gula merah (traditional brown sugar) industry in promoting the economic empowerment of the community of Huta Tinggi Village, Puncak Sorik Merapi District, Mandailing Natal Regency. Conducted by KKN students of Group 33, the research used a qualitative approach: field observation, in-depth interviews with business actors, and documentation of the production process. The main findings indicate that the gula merah industry significantly increases household incomes, creates local employment, and strengthens an economy grounded in traditional wisdom. The still-traditional production process functions as a cultural identity and presents an opportunity to increase added value through packaging innovation, quality improvement, certification, and digital marketing. Identified challenges include limited equipment, low quality standards, minimal promotion, and restricted market access. Practical recommendations include technical training and quality management for producers, investment in simple equipment, assistance with packaging and branding, guidance on digital marketing, and facilitation of market access and microfinance by local government. Partnerships with educational institutions and the private sector are also advised for product research, halal and quality certification, and research to support product diversification. In conclusion, the Huta Tinggi gula merah industry is not only economically valuable but also strategic for rural community empowerment; implementing these recommendations through immediate actions, such as training, financing access, and digital promotion, combined with regular monitoring and evaluation can sustainably strengthen local economic resilience and engage younger generations.